1995
DOI: 10.1007/bf02770999
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential fluctuations of human T-lymphocytes have fractal characteristics of fractional brownian motion

Abstract: The voltage across the cell membrane of human T-lymphocyte cell lines was recorded by the whole cell patch clamp technique. We studied how this voltage fluctuated in time and found that these fluctuations have fractal characteristics. We used the Hurst rescaled range analysis and the power spectrum of the increments of the voltage (sampled at 0.01-sec intervals) to characterize the time correlations in these voltage fluctuations. Although there was great variability in the shape of these fluctuations from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 21 publications
0
24
1
Order By: Relevance
“…The rescaled range analysis was also used by Churilla et al (1996) to study the #uctuations of the membrane potential of human T-lymphocytes. They showed that the phenomenon has the fractal characteristics of a fractional Brownian motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rescaled range analysis was also used by Churilla et al (1996) to study the #uctuations of the membrane potential of human T-lymphocytes. They showed that the phenomenon has the fractal characteristics of a fractional Brownian motion.…”
Section: Discussionmentioning
confidence: 99%
“…In cellular biology, the rescaled range analysis has been used to analyse records in time produced by the mechanical motions of cells growing in tissue culture (Giaever & Keese, 1989) and one of us applied the R/S analysis to the study of patch clamp records of the membrane potential #uctuations of human T-lymphocytes (Churilla et al, 1996). Here the R/S analysis is applied to study calcium-activated potassium channels of Leydig cells.…”
Section: Introductionmentioning
confidence: 99%
“…This crossover implies a transition from an absence of correlations in the signal to antipersistence behavior. Similar transitions from short-to long-time behavior have been observed for other physiological time series [16][17]. Because the mean square displacement is related to the entropy S of the signal, S ~ ln Δ (where ln denotes the natural logarithm), the plateau value can be used to characterize the sEMG signal [15].…”
Section: Introductionmentioning
confidence: 85%
“…26,27 Moreover, electrophysiological studies showed the presence of fractal characteristics in the oscillations of the membrane potential. 28 Also, it was shown that, while isolated cardiac cells beat stochastically, fractal patterns of activity establish when a large number of cells are electrically coupled and synchronize. 29 Finally, it is feasible that other processes, such as biochemical reactions, protein synthesis, or gene expression, contribute to the observed variations in beat rate.…”
Section: Intrinsic Power-law Behavior: Possible Mechanismsmentioning
confidence: 99%